2008
DOI: 10.1007/s10162-008-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Topography of Auditory Nerve Projections to the Cochlear Nucleus in Cats after Neonatal Deafness and Electrical Stimulation by a Cochlear Implant

Abstract: We previously reported that auditory nerve projections from the cochlear spiral ganglion (SG) to the cochlear nucleus (CN) exhibit clear cochleotopic organization in adult cats deafened as neonates before hearing onset. However, the topographic specificity of these CN projections in deafened animals is proportionately broader than normal (less precise relative to the CN frequency gradient). This study examined SG-to-CN projections in adult cats that were deafened as neonates and received a unilateral cochlear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…Surprisingly, despite the significantly shorter deafness durations and higher SGC survival, training-induced enhancements in temporal following ability in these animals remained significantly below that of behaviorally trained long-deaf animals [LDS(ϩ) group]. These findings underscore that the potent efficacy of training-induced temporal plasticity is not limited by long-term deafness and its deleterious effects on peripheral (e.g., Leake and Hradek 1988;Vollmer et al 2007) and central morpholog (e.g., Leake et al 2008;Lustig et al 1994;Nishiyama et al 2000).…”
Section: Discussionmentioning
confidence: 65%
“…Surprisingly, despite the significantly shorter deafness durations and higher SGC survival, training-induced enhancements in temporal following ability in these animals remained significantly below that of behaviorally trained long-deaf animals [LDS(ϩ) group]. These findings underscore that the potent efficacy of training-induced temporal plasticity is not limited by long-term deafness and its deleterious effects on peripheral (e.g., Leake and Hradek 1988;Vollmer et al 2007) and central morpholog (e.g., Leake et al 2008;Lustig et al 1994;Nishiyama et al 2000).…”
Section: Discussionmentioning
confidence: 65%
“…Alteration in the SG neuronal membrane properties or channels also could account for the observed EABR threshold reductions. Alternatively, it should also be noted that previous animal studies have shown that lower EABR thresholds are correlated with better SG survival in the cochlear region near the stimulating electrodes (Leake et al 2008b). Thus, it may be possible that some neurons initially unresponsive to electrical stimulation, due to ototoxic drug administration effects, become viable and responsive during BDNF treatment.…”
Section: Longitudinal Eabr Threshold Datamentioning
confidence: 98%
“…Electrical stimulation from a CI has also been shown to promote SG survival in vivo in deafened adult guinea pigs (Hartshorn et al 1991;Kanzaki et al 2002;Lousteau 1987;Miller 2001;Miller and Altschuler 1995;Mitchell et al 1997) and in cats deafened early in life (Leake et al 1999(Leake et al , 2007(Leake et al , 2008b). In our laboratory, studies of cats deafened prior to hearing onset have shown that multichannel CI electrical stimulation applied over several months results in substantial improvement in SG neural survival (Leake et al 1999(Leake et al , 2007(Leake et al , 2008a above that seen in the contralateral deafened cochleae. Other studies, however, have not found evidence of trophic effects of electrical stimulation (Araki et al 1998;Coco et al 2007;Li et al 1999;Shepherd et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital images of sections were captured using a Zeiss Axioskop 2, a 2.5× objective and a Zeiss AxioCam MRc5 digital camera. Cytoarchitectural criteria according to Kiang et al, (1975); Leake et al, (2002); Leake et al,(2008); Stakhovskaya et al, (2008) were utilized to outline the three individual CN subdivisions in each imaged section (excluding the cochlear nerve root). The boundary between the DCN and the PVCN was defined by the intermediate acoustic stria in caudal sections and using the granule cell layer as a landmark in more rostral sections.…”
Section: Methodsmentioning
confidence: 99%